Screening of various parameters of enterobacter aerogenes batch culture for biohydrogen production - Mohamad Puad, Noor Illi; Mamat, Nur Amira; Azmi, Azlin Suhaida (International Association of Computer Science & Information Technology (IACSIT ) Press, 2016)
Hydrogen (H2) gas has been widely known as a potential renewable energy. Throughout the advancements of technologies, a method of producing H2 gas which is known as biohydrogen was developed. Biohydrogen has a potential to solve the current greenhouse effects since it is an eco-friendly and harmless gas that is operated at ambient temperature and atmospheric pressure using renewable substrates as a source. In this study, Enterobacter aerogenes (E. aerogenes) was used as the biohydrogen producing microorganism. The parameters that influence the biohydrogen production such as glucose, glycerol, initial pH, inoculum size, tryptone, yeast extract, agitation rate and temperature were screened using Plackett-Burman design tool (Design Expert 6.08 software). The results were analyzed using Minitab 17 software and fitted into the secondary-order polynomial regression equation for further analysis. Based on the results, for the bioreactor fermentation, glucose, glycerol, tryptone, inoculum size and agitation rate have negative effects to the biohydrogen production whereas initial pH, yeast extract and temperature gave positive effects. For the shake flask experiments, some of the low level of the parameters gave greater influence on hydrogen yield (glucose, tryptone, agitation rate and temperature) while some of the high level of the parameters gave greater influenced on the hydrogen yield (glycerol, initial pH, inoculum size and yeast extract). The highest hydrogen yield achieved in the bioreactor was 10 ppm while in the shake flask experiments, the highest yield recorded was 24 ppm.